2016
DOI: 10.1126/sciimmunol.aaf7153
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 inhibition resets defective human central B cell tolerance

Abstract: The 1858T protein tyrosine phosphatase nonreceptor type 22 (PTPN22 T) allele is one of the main risk factors associated with many autoimmune diseases and correlates with a defective removal of developing autoreactive B cells in humans. To determine whether inhibiting PTPN22 favors the elimination of autoreactive B cells, we first demonstrated that the PTPN22 T allele interfered with the establishment of central B cell tolerance using NOD-scid-common γ chain knockout (NSG) mice engrafted with human hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 28 publications
5
53
0
Order By: Relevance
“…In agreement with this hypothesis, we demonstrated that a lentiviral-driven expression of 620W PTPN22 variant in human B cells that developed in humanized mice was sufficient to abrogate central B-cell tolerance, whereas the expression of the common 620R PTPN22 had no impact on the functionality of this tolerance checkpoint 52. In agreement with this hypothesis, we demonstrated that a lentiviral-driven expression of 620W PTPN22 variant in human B cells that developed in humanized mice was sufficient to abrogate central B-cell tolerance, whereas the expression of the common 620R PTPN22 had no impact on the functionality of this tolerance checkpoint 52.…”
supporting
confidence: 79%
“…In agreement with this hypothesis, we demonstrated that a lentiviral-driven expression of 620W PTPN22 variant in human B cells that developed in humanized mice was sufficient to abrogate central B-cell tolerance, whereas the expression of the common 620R PTPN22 had no impact on the functionality of this tolerance checkpoint 52. In agreement with this hypothesis, we demonstrated that a lentiviral-driven expression of 620W PTPN22 variant in human B cells that developed in humanized mice was sufficient to abrogate central B-cell tolerance, whereas the expression of the common 620R PTPN22 had no impact on the functionality of this tolerance checkpoint 52.…”
supporting
confidence: 79%
“…Both the HC donor and the HC NSG mouse contained only 10% autoreactive B cells in their spleens, consistent with previous results. 37 For the RA donor, this defect was confirmed by the high percentage (50%) of B-cell clones making human epithelial type 2-binding antibodies in the RA donor and respective PI mouse compared with the HC patient ( Figure 5B). …”
Section: Resultsmentioning
confidence: 73%
“…Consistent with this possibility, mice carrying a mutation in Ptpn22 (R619W) analogous to the disease-associated human PTPN22 allele (R620W) had a B cell-autonomous defect that could promote autoimmunity and was associated with the protection of immature B cells from apoptosis 131 . Moreover, in mice engrafted with human haematopoietic stem cells, intrinsic expression of the R620W allele was sufficient to impair B cell central tolerance 132 .…”
Section: Central Tolerance In Human B Cellsmentioning
confidence: 99%